2016
DOI: 10.1021/acscatal.6b03004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Linker Length on Selectivity and Cooperative Reactivity in Platinum-Catalyzed Asymmetric Alkylation of Bis(phenylphosphino)alkanes

Abstract: The selectivity of catalytic asymmetric transformations of bifunctional symmetrical substrates often depends on the linker between the two reactive sites. If the catalyst controls the selectivity of reactions at both sites, the rac product will be formed in high enantiomeric ratio (er) via asymmetric amplification. Substrate control may augment this selectivity (positive cooperativity) or detract from it (negative cooperativity). Here, we investigated the effect of linker length on the selectivity of catalytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…Asymmetric alkylation or arylation of racemic secondary phosphines, catalyzed by chiral Lewis acids, in many cases led to the formation of enantiomerically enriched tertiary phosphines [105][106][107][108][109][110][111][112]. For example, the chiral platinum complex Pt(Me-Duphos)(Ph)(Br) catalyzed the asymmetric alkylation of secondary phosphines with benzyl halides to form tertiary phosphines (or their boranes) in good yields and with 50-93% ee (Equation (77)) [107].…”
Section: Electrophilic Asymmetric Catalysismentioning
confidence: 99%
See 2 more Smart Citations
“…Asymmetric alkylation or arylation of racemic secondary phosphines, catalyzed by chiral Lewis acids, in many cases led to the formation of enantiomerically enriched tertiary phosphines [105][106][107][108][109][110][111][112]. For example, the chiral platinum complex Pt(Me-Duphos)(Ph)(Br) catalyzed the asymmetric alkylation of secondary phosphines with benzyl halides to form tertiary phosphines (or their boranes) in good yields and with 50-93% ee (Equation (77)) [107].…”
Section: Electrophilic Asymmetric Catalysismentioning
confidence: 99%
“…For example, the chiral platinum complex Pt(Me-Duphos)(Ph)(Br) catalyzed the asymmetric alkylation of secondary phosphines with benzyl halides to form tertiary phosphines (or their boranes) in good yields and with 50-93% ee (Equation (77)) [107]. Secondary phosphines with bulky substituents (Ar') reacted with para-substituted aryl iodides to form tertiary phosphines with an enantiomeric excess up to 88% [105,106]. Glueck [106,107] reported that racemic secondary phosphines in the presence of Pt(Me-Duphos)(Ph)(Br) and NaOSiMe 3 in toluene afforded adducts 4 which interconvert rapidly by P-inversion (S P )-4…”
Section: Electrophilic Asymmetric Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…In the latter case, two stereogenic centers are formed simultaneously in the first step and no influence on the diastereomeric product ratio should be expected when the enantiomeric excess of the catalyst is changed. 18 Significant changes in dr were otherwise observed in the hydrogenation of 1c upon variation of the ee of the catalyst precursor 5b (Figure 3), from dr = 1.0 with rac-5b to dr = 3.6 with 5b. These observations are in accord with a substrate decoordination between the generation of the first and second stereogenic centers, suggesting that path a is operating in the present hydrogenation reactions.…”
mentioning
confidence: 93%
“…Asymmetric metal catalyzed hydrophosphination and phosphination is well known with palladium, platinum, and ruthenium metals in the presence of different types of bidentate chiral phosphine ligands. Glueck and co‐workers demonstrated that palladium can be used for enantioselective phosphination reaction in combination with ( S , S ) Me‐DUPHOS ligand (Figure ) . In their attempts to synthesize enantiopure P‐stereogenic phosphines (not urea containing), Glueck and co‐workers achieved 88 % enantiomeric excess ( ee ).…”
Section: Introductionmentioning
confidence: 99%